To Compare the Efficacy Of 1% Chloroprocaine Alone And 1% Chloroprocaine with Fentanyl in Infraumbilical Surgical Operations Performed Under Spinal Anaesthesia - P Pradeep; Sachin D Joshi; Uma Maheshwara Rao W (Academia Anesthesiologica International, 2019)
Background: Spinal anaesthesia is a dependable and secure method for performing surgery on the lower abdomen, perianal area, and lower limbs. The recent availability of short-acting local anaesthetic drugs, such as preservative-free 1% chloroprocaine, has sparked fresh interest in using this approach for short and ultra-short operations. Opioids remain the most often used additives in local anaesthetics to enhance the pain-relieving effects. Aim: To compare the efficacy of 1% chloroprocaine alone and 1% chloroprocaine with fentanyl in infraumbilical surgical operations performed under spinal anaesthesia. Subjects and Methods: A total of 120 patients, aged between 20 and 70 years, of either gender, with ASA grade I and II, weighing between 38 and 68 kg, and with a height between 150 and 170 cm, were scheduled for elective infraumbilical surgery lasting less than 60 minutes. The patients were randomly assigned to two groups using the envelope technique. Group C received 3.0 mL of 1% Chloroprocaine mixed with 0.5 mL of normal saline, whereas Group CF received a 3 mL of 1% Chloroprocaine mixed with 25 μg of fentanyl (0.5 mL). During the surgical procedure, intravenous (i.v.) access was established and patients were administered a preload of 10 mL/kg of Ringer lactate over a period of 15 minutes. All standard monitors, such as noninvasive blood pressure, pulse oximetry, and three-lead electrocardiogram, were attached. Results: In group CF, the average time it took to achieve motor block was 8.88±1.06 minutes, which was sooner compared to group C, where it took 11.36±1.27 minutes (P=0.001). In our investigation, the average time it took for the sensory block to start at the T10 dermatomal level was shorter in the group that received 1% Chloroprocaine with Fentanyl (6.66±0.48 minutes) compared to the group that received just 1% Chloroprocaine (9.24±0.58 minutes) (P = 0.001). The highest sensory level dermatome in 36 individuals in Group C was seen between T6 and T9, while in Group CF, this was observed in 50 patients. 24 patients in Group C achieved the highest levels of T10-T12, compared to 10 patients in Group CF. The average length of sensory block was significantly longer in group CF compared to group C (94.58±3.97 min vs 82.28±3.61 min, p = 0.001). The Visual Analogue Scale (VAS) at the time of first pain relief was 4.08±0.87 in Group C and 3.11±0.81 in Group CF (p=0.001). In Group C, the time for initial mobilisation was 124.39±3.61 minutes, but in Group CF it was 162.25±3.87 minutes (p=0.001). Conclusion: Our findings indicate that the use of 2-Chloroprocaine leads to prompt alleviation of sensory and motor blockage, as well as early mobilisation and release for procedures lasting less than 60 minutes. Our research indicates that incorporating intrathecal Fentanyl as a supplementary agent to 2 - Chloroprocaine in the correct dosage is a superior option.